2014
DOI: 10.3389/fpsyg.2014.01302
|View full text |Cite
|
Sign up to set email alerts
|

Word reading and translation in bilinguals: the impact of formal and informal translation expertise

Abstract: Studies on bilingual word reading and translation have examined the effects of lexical variables (e.g., concreteness, cognate status) by comparing groups of non-translators with varying levels of L2 proficiency. However, little attention has been paid to another relevant factor: translation expertise (TI). To explore this issue, we administered word reading and translation tasks to two groups of non-translators possessing different levels of informal TI (Experiment 1), and to three groups of bilinguals possess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 59 publications
4
29
0
Order By: Relevance
“…3) were statistically significantly different (F (3,8) = 74.36, p < 0.001). For instance, the response time during C2E (47.29 ± 8.73 s) was the longest among the four conditions, followed by E2C (41.20 ± 7.92 s), E (24.82 ± 1.72 s), and C (21.19 ± 2.66 s).…”
Section: Behavioral Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…3) were statistically significantly different (F (3,8) = 74.36, p < 0.001). For instance, the response time during C2E (47.29 ± 8.73 s) was the longest among the four conditions, followed by E2C (41.20 ± 7.92 s), E (24.82 ± 1.72 s), and C (21.19 ± 2.66 s).…”
Section: Behavioral Resultsmentioning
confidence: 97%
“…Recent work has validated translation asymmetry, which is characterized as the asymmetrical levels of cognitive cost between forward translation (translating from L1 to L2) and backward translation (translating from L2 to L1) [1][2][3]. However, the neural correlates of translation have not been studied in depth.…”
Section: Introductionmentioning
confidence: 99%
“…However, the discussion of how interpreting experience modulates lexical processing and comprehension could also be enriched by findings from studies involving translators. García et al (2014) claim explicitly that strictly linguistic effects of translation experience may be independent of the modality, i.e., they would be similar in the case of interpreting and translation. This is juxtaposed with executive functions that might be more prone to change due to time constraints experienced by interpreters.…”
Section: Effects Of Training and Experience In Lexical Access And Commentioning
confidence: 97%
“…What follows is a review of lexical processing studies involving translators performing tasks that focused on comprehension. García et al (2014) studied word reading and word translation tasks performed by groups differing in translation experience: beginner translation trainees, advanced translation trainees and professional translators. They found that beginner trainees were significantly slower in general than translators and advanced trainees, while the latter two groups did not differ.…”
Section: Effects Of Training and Experience In Lexical Access And Commentioning
confidence: 99%
“…We can summarize that these participants were truly multilingual and highly proficient. The degree of bilingualism is routinely reported in the literature because it has an effect on behaviour during translation [45].…”
Section: Participantsmentioning
confidence: 99%